Theory of Differential Conductance of Co on Cu(111) including Co s and d Orbitals, and Surface and Bulk Cu States - Fernández, Joaquín (2021)
We revisit the theory of the Kondo effect observed by a scanning-tunneling microscope (STM) for transition-metal atoms (TMAs) on noble-metal surfaces, including d and s orbitals of the TMA, surface and bulk conduction states of the metal, and their hopping to the tip of the STM. Fitting the experimentally observed STM differential conductance for Co on Cu(111) including both the Kondo feature near the Fermi energy and the resonance below the surface band, we conclude that the STM senses mainly the Co s orbital and that the Kondo antiresonance is due to interference between states with electrons in the s orbital and a localized d orbital mediated by the conduction states.